Soil particle accumulation in termite (Macrotermes bellicosus) mounds and the implications for soil particle dynamics in a tropical savanna Ultisol - Abe, S.S.; Kotegawa, T.; Onishi, T.; Watanabe, Y.; Wakatsuki, T. (Wiley, 2012)
This study investigated the influence of mound-building termites on soil particle dynamics on the land surface and in soil-forming processes by examining the amount of soil particles in mound structures of Macrotermes bellicosus in a highly weathered Ultisol of tropical savanna. Soil particle turnover via the mounds was estimated using particle stock data and soil turnover data from previous studies. A 4-ha study plot with six mounds of relatively uniform shape and size was investigated. Soil mass constituting the mounds was 6,166 ± 1,581 kg mound−1 within which the mound wall and nest body accounted for 5,002 ± 1,289 and 1,164 ± 293 kg, respectively. The mound wall contained a significantly larger amount of clay (252 ± 9.97 g kg−1) balanced with a lower sand content (676 ± 26.5 g kg−1) than in the adjacent surface (Ap1) horizon, (46.4 ± 12.8 g clay kg−1; 866 ± 83.2 g sand kg−1); the nest body had much higher clay content (559 ± 51.0 g kg−1) but less sand (285 ± 79.2 g kg−1) than the mound wall. As a result, the mounds of M. bellicosus accumulated clay of 2,874 ± 781 kg ha−1 (corresponding to 2.52% of clay stock in the Ap1 horizon) along with an estimated clay turnover rate of 169 kg ha−1 year−1. These findings suggest a positive feedback effect from termite mound-building activity on soil particle dynamics in tropical savanna ecosystems: M. bellicosus preferentially use subsoil material for mound construction, resulting in relocation of illuvial clay in the subsoil to the land surface where clay eluviation from the surface soil and its illuviation in the subsoil are major soil-forming processes.